Role of mitochondrial dysfunction and altered autophagy in cardiovascular aging and disease: from mechanisms to therapeutics - Marzetti, Emanuele; Csiszar, Anna; Dutta, Debapriya; Balagopal, Gauthami; Calvani, Riccardo; Leeuwenburgh, Christiaan (American journal of physiology. Heart and circulatory physiology, 2013)
Advanced age is associated with a disproportionate prevalence of cardiovascular disease (CVD). Intrinsic alterations in the heart and the vasculature occurring over the life course render the cardiovascular system more vulnerable to various stressors in late life, ultimately favoring the development of CVD. Several lines of evidence indicate mitochondrial dysfunction as a major contributor to cardiovascular senescence. Besides being less bioenergetically efficient, damaged mitochondria also produce increased amounts of reactive oxygen species, with detrimental structural and functional consequences for the cardiovascular system. The age-related accumulation of dysfunctional mitochondrial likely results from the combination of impaired clearance of damaged organelles by autophagy and inadequate replenishment of the cellular mitochondrial pool by mitochondriogenesis. In this review, we summarize the current knowledge about relevant mechanisms and consequences of age-related mitochondrial decay and alterations in mitochondrial quality control in the cardiovascular system. The involvement of mitochondrial dysfunction in the pathogenesis of cardiovascular conditions especially prevalent in late life and the emerging connections with neurodegeneration are also illustrated. Special emphasis is placed on recent discoveries on the role played by alterations in mitochondrial dynamics (fusion and fission), mitophagy, and their interconnections in the context of age-related CVD and endothelial dysfunction. Finally, we discuss pharmacological interventions targeting mitochondrial dysfunction to delay cardiovascular aging and manage CVD.